2019
DOI: 10.1063/1.5088868
|View full text |Cite
|
Sign up to set email alerts
|

Band structure and thermoelectric performances of antimony under trigonal transformation

Abstract: Ab initio calculation and Boltzmann transport equation have been integrated to find the fundamental influences of trigonal transformation on band structures and thermoelectric performances of antimony. Calculations reveal that antimony could keep its semimetal feature within the c/a range of 2.27–2.82 and that two transitions of band structures of antimony under trigonal transformation are revealed for the first time. Moreover, trigonal transformation has a significant influence on the thermoelectric performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In terms of application potential, we note that trigonally deformed Sb (like simple cubic Sb) has recently been predicted to feature superior thermoelectrical performance over β-Sb. 56 Given that monolayered 2D β-Sb has been predicted to surpass all other pristine 2D materials in terms of thermoelectric performance, 27 future studies on band structure and electronic properties of the here observed β-Sb[2-21]/cubic Sb(001) deposits merit consideration. c,d) and cubic Sb(001) viewed along [001] zone axis (e,f,g), respectively.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In terms of application potential, we note that trigonally deformed Sb (like simple cubic Sb) has recently been predicted to feature superior thermoelectrical performance over β-Sb. 56 Given that monolayered 2D β-Sb has been predicted to surpass all other pristine 2D materials in terms of thermoelectric performance, 27 future studies on band structure and electronic properties of the here observed β-Sb[2-21]/cubic Sb(001) deposits merit consideration. c,d) and cubic Sb(001) viewed along [001] zone axis (e,f,g), respectively.…”
Section: Resultsmentioning
confidence: 93%
“…[54][55][56] While the existence of cubic Sb in bulk form has been a long-standing matter of debate in literature, [52][53][54][55][56] cubic Sb is typically associated with high pressure conditions but has also been reported to occur in Sb thin films, presumably formed via substrate-induced stress. [47][48][49][50][51][52][53][54][55][56] Notably, structurally β-Sb [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (and AA α-Sb multilayers) and cubic Sb(001) structures are all closely related and may gradually transition into each other. 31,[54][55][56] This makes their differentiation difficult and partly ambiguous.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transport properties are derived as a function of temperature and chemical potential employing the constant relaxation time approximation (CRTA), which neglects the weak energy dependence of relaxation time (τ) but retains some temperature and doping dependence. [29,30] Based on the RBA, [31][32][33] the temperature and carrier density (n) only shift the Fermi energy but keep the invariance of the energy band shape. [11,34] The phonon spectrum and lattice thermal conductivity are calculated by combining the lattice dynamics and phonon Boltzmann transport equations implemented in Phonopy [35] and ShengBTE [36] package.…”
Section: Theoretical Methodsmentioning
confidence: 99%